A Method for Extraction of Text from Image file and Number Plate of Vehicle: A High Performance Scheme for Text Extraction and Number Plate Recognition (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In the computer vision research area Image text extraction and extract number from vehicle number plate is a well-known problem. Planned picture details, organizing of pictures, content-based data indexing and recovery depend on the textual data demonstration in those images. Its challenging and difficult job to take away content from images due to the variations in the content, for example, content scripts, style, text style, size, shading, arrangement and orientation and because of external factors, for example, low picture differentiate (textual) and complex background.Investigational outcomes on different dataset illustration that proposed scheme leads to a high performance.